A second order L0 stable algorithm for evaluating European options. (2nd May 2007) - Thulasiram, Ruppa K.; Zhen, Chen; Chhabra, Amit; Thulasiraman, Parimala; , Abba B. Gumel
In this paper, we study the option pricing problem, one of the prominent and challenging problems in computational finance. Using the Pade approximation, we have developed a second order L0 stable discrete parallel algorithm for experimentation on advanced architectures. We have implemented the sequential version of this algorithm and evaluated the European Options. Numerical results are compared with those obtained using other commonly used numerical methods and shown that the new algorithm is robust and efficient than the traditional schemes. Also, using explicit Forward Time Centered Space (FTCS) on the reduced Black-Scholes partial differerential equation, we report pricing of European options. We have done our experiments on a shared memory multiprocessor machine using OpenMP and report a maximum speedup of 3.43 with 16 threads.